What LED to the Boom? Unpacking China's Development Cooperation in Latin America. (December 2019) - Malacalza, Bernabé
What led to the boom of Chinese development cooperation in Latin America? This article provides a systematic analysis of China's foreign behavior, motives, and policies regarding development cooperation toward the region between 2000 and 2014. I propose a comparative framework that defines Chinese development cooperation as a tool of economic diplomacy. Drawing on empirical evidence from AidData's Global Chinese Official Finance Dataset and Chinese white papers on foreign aid, the findings evidence that China was motivated by multiple and conjunctural factors in providing development cooperation. In the realm of theory, the article contributes to the literature on economic statecraft—filling in gaps in understanding the relationship between economics and politics. Empirically, it provides a set of tools for understanding the important role that development cooperation plays in a nation's statecraft. Regarding Chinese foreign policy studies, it offers insight into the financial dimension of China's international economic relations.